Design of thin wall structures for energy absorption applications: Enhancement of crashworthiness due to axial and oblique impact forces - Tarlochan, F.; Samer, F.; Hamouda, A.M.S.; Ramesh, S.; Khalid, Karam (Thin-walled structures, 2013)
This paper describes a computationally aided design process of a thin wall structure subject to dynamic compression in both axial and oblique directions. Several different cross sectional shapes of thin walled structures subjected to direct and oblique loads were compared initially to obtain the cross section that fulfills the performance criteria. The selection was based on multi-criteria decision making (MCDM) process. The performance parameters used are the absorbed crash energy, crush force efficiency, ease of manufacture and cost. Once the cross section was selected, the design was further enhanced for better crash performances by investigating the effect of foam filling, increasing the wall thickness and by introducing a trigger mechanism. The outcome of the design process was very encouraging as the new design was able to improve the crash performance by an average of 10%. •Crashworthiness characteristics of tubular profiles were investigated based on axial and oblique loading.•The energy absorbed by the tubes due to oblique loading is much lower than for direct loading.•As the perimeter keeps increasing, so will the energy absorption capabilities.•Hexagonal, octagonal and circular are considered to be good geometry.•In general, foam filling does improve the crash performance indicators.